Preparation and characterization of core-shell copper nanoparticles stabilized by kappa carragenan and sodium alginate - Khanehzaei, Hajar (2015)
Among metal nanoparticles, copper nanoparticles (Cu-NPs) have recently attracted increased attention because of their low cost (in contrast to Au and Ag) and their usable properties. Rate of resistance of microorganisms to antibiotics is alarming. Pathogenic bacteria are becoming much resistant to antibiotics. Copper nanoparticles synthesis particularly in bio-based stabilizers can act as antimicrobial agents, which in turn could resist pathogenic microorganisms. In this work, synthesis and characterization of Cu-NPs and Cu@Cu2O core shell nanoparticles (CSNPs) were carried out in the presence of two different marine polymers as stabilizers Kappaphycus alvarezii (K. alvarezii) and sodium alginate (SA) by two varied methods;chemical reduction and gamma irradiation. The aim of this research is to synthesize, characterize and test the antimicrobial activity of Cu and Cu2O nanoparticles. The Cu@Cu2O-CSNPs were synthesized by using chemical reduction method in K. alvarezii media. Also Cu-NPs and Cu@Cu2O -CSNPs were prepared in sodium alginate by using same method. The synthesis carried out using aqueous medium in presence of hydrazinium hydroxide as reducing agent, CuSO4.5H2O as copper precursor and sodium hydroxide as pH moderator. The effects of the concentration of K. alvarezii and sodium alginate as stabilizer were studied. Formation of nanoparticles was determined by UV–vis spectroscopy where surface plasmon absorption maxima can be observed at 390-600 nm from the UV–vis spectrum. The synthesized nanostructures were also characterized by X-ray diffraction (XRD). In addition; the morphology and structure of the nanoparticles were investigated by Transmission Electron Microscopy (TEM), emission scanning electron microscopy (FESEM) and Energy-dispersive X-ray spectroscopy (EDX). TEM results showed a gradual decrease of particle size from low concentration of K. alvarezii and sodium alginate to high concentration. The study clearly showed that using various amounts of K. alvarezii and sodium alginate led to produce Cu@Cu2O-CSNPs with different sizes and ratios of Cu:Cu2O. For the K. alvarezii/Cu@Cu2O-CSNPs, the Cu-NPs increased and the Cu2O decreased with increasing the concentration of K. alvarezii until 0.2 wt.% in the Cu@Cu2O-CSNPs. At the highest concentration of K. alvarezii, Cu decreased compare to Cu2O. Moreover for the Cu@Cu2O-CSNPs synthesized in sodium alginate with increasing the media concentration, the Cu increased and at the highest concentration of media (1.0 wt.%) only copper nanoparticles were produced. The size of the nanoparticles decreased as the amount of K. alvarezii and sodium alginate was increased. Moreover the K. alvarezii/Cu@Cu2O-CSNPs and SA/Cu-NPs were synthesized by using gamma irradiation method. The synthesis was done through γ-irradiation reduction of copper ions. The suspension was irradiated under γ-irradiation source 60Co with doses of 5, 20, 40, 80, 100 and 120 kGy at room temperature. The effect of irradiation dosage was investigated. The UV-Vis spectroscopy results obtained for samples indicated that only the samples which were irradiated by 80, 100 and 120 kGy showed surface plasmon resonance (SPR) peaks in the range of 350-600 nm. It was due to the formation of K. alvarezii/Cu@Cu2O-CSNPs and SA/Cu-NPs for these doses. TEM analysis indicated size and distribution of the nanoparticles varied in different doses of gamma irradiation. When the absorbed dose increased from 80 to 120 kGy the nanoparticle size decreased. Following synthesis of the nanoparticles, antibacterial analysis of the synthesized particles was investigated. Antimicrobial analysis conducted on the synthesized nanoparticles showed activity against all tested microorganisms.